Pelatihan Aplikasi E-PONPES sebagai Upaya Peningkatan Manajemen Pengelolaan Data dan Donasi Pondok Pesantren Riyadus Sholihin - Husni Faqih; Rousyati Rousyati; Husni Mubarok (Madani : Indonesian Journal of Civil Society, 2022)
Community Service is an integral part of the Tri Dharma of Higher Education which aims to increase the level of intelligence in the lives of many people around the campus, the curiosity of learning interests of the board members and students of the Riyadus Sholihin Islamic Boarding School to increase the scientific repertoire of improving data management and donations that are accurate and effective and efficient. The data analysis method was processed using a mixed qualitative and quantitative descriptive method to describe the characteristics and tendencies of respondents towards the training of the E-Ponpes application from primary and secondary data. The routine of PkM activities carried out by Lecturers of the Faculty of Engineering and Informatics UBSI Tegal Campus who are members of PkM in collaboration with Riyadus Sholihin Islamic Boarding School in carrying out face-to-face events by complying with health protocols. The results are very unique from the 10 respondents participating in the E-Ponpes Application training where interestingly the participants are very enthusiastic to learn to explore the E-Ponpes Application with the initial test results of 100% with less predicate and 83% final test with the good predicate.